The Mameluke or slave dynasty of Egypt, 1260-1517 A.D. - Muir, William‏, Sir, 1819-1905. (Piscataway, NJ)
xxxii, 245 sayfa, [11] sayfa resim, harita
Keywords: “Alert to the implications of Egyptian politics to the world of the Middle Ages, Muir offers a detailed look at the rule of the slave-soldier caste known as the Mamelukes who ruled Egypt from 1260 to 1517. Each ruler of the Bahrite and Circassian dynasties is given a full chapter, and the role of the Mamelukes under the Ottoman Empire is reviewed“ -- Yayıncı.